PRESERVASI NASKAH KLASIK - Faizal Amin (Khatulistiwa, 2011)
This paper elaborates somes aspecs of manuscript and it‘s preservation. This significant leads us to understand the needs to move together hand in hand to preserve an inundate number of manuscripts in Nusantara. The grand design of manuscript preservation covers phisic and text. The phisic preservation devided into preventif and curatif conservation. On the other hand, text preservation related to digitalization, philology study, and rewriting. To obtain the goals, this paper will begin to describe the concept of manuscript and than the modes of preservation.